Tacitus: An Emperor and his Aegis - Bontas, Andrei (KOINON: The International Journal of Classical Numismatic Studies, 2021)
Although he ruled briefly during a highly volatile period, Tacitus had a varied mass of billon/base metal coins minted in his name from a variety of mints both in the East and in the West. And the series are sometimes as complex as one would expect from an emperor with a longer reign, rather than an emperor who did not stay in power for a full year. This short note deals with one particular, peculiar and particularly rare strike, coming in the context of an overly-abundant series minted at Rome from around the beginning to mid 276, represented by the image at Figure 1.